Affective Meaning Found in 'Nothing's Gonna Change My Love for You" - Rafael, Steven; Adestina, Desi; Siregar, Otto (Linguistics and ELT Journal, 2024)
This study examines the affective semantic meaning of the lyrics of the song "Nothing's Gonna Change My Love For You". This study uses a qualitative approach to analyze the affective meaning in the lyrics of the song. In this study, G. Leech's theory of affective meaning is used to identify and analyze the emotional responses conveyed through certain words and phrases in the song. Data collection involved downloading the song, reading the lyrics, and identifying the emotional tone in the text. This study refers to the emotional impact of words and their important role in song lyrics, as songs often aim to evoke emotions such as love, happiness, or sadness. The results of the Analysis of the lyrics of "Nothing's Gonna Change My Love For You" are that the song contains twelve different emotional meanings—ten positive and two negative. Positive emotions focus on themes of love, commitment, and certainty, while negative emotions reflect dependence and longing. These findings demonstrate the power of carefully chosen words in shaping the emotional experience of the listener and the relationship between the singer and the audience. This study highlights the influence of affective meaning in songs and how it shapes emotional engagement, highlighting the important role of language in evoking strong feelings and creating emotional resonance.